SYI‘AH ITSNA ‘ASYARIYAH: Beberapa Prinsip Ajaran - Zulkarnaen Zulkarnaen (State Islamic University North Sumatra, 2008)
Abstract: Syi‘ah Itsna ‘Asyariyah: Some Principal Teachings. The debate of ideological understanding of the rightful leadership is an important issue within the Shiates mainstream of Islam. The Shiates put ‘Ali—the fourth of al-khulafâ’ al-râsyidûn—in a special position, because they consider him as the rightful successor of the Prophet Muhammad. On the contrary, however, they consider the other three caliphs as unlawful claimers to the caliphate. However, differences of understanding in the Shiates also occur at doctrinal level that gives rise to the emergence of the Twelvers and Seveners of Shiates, the former of which holds that there are twelve lawful number of imâm whereas the latter believes that there are only seven respectively. This article traces the historical roots of divergent doctrine within the Shiites mainstream, analyses how it develop through times, and argues that the different doctrine hold by respective sects whether at a lesser or greater extent lead to different factions. Kata Kunci: syi‘ah itsna ‘Asyariyah, imâmah